The Relationship between Actual Fundamental Motor Skill Proficiency, Perceived Motor Skill Confidence and Competence, and Physical Activity in 8-12-Year-Old Irish Female Youth - Orlagh Farmer; Sarahjane Belton; Wesley O'Brien (MDPI AG, 2017)
This study examines the relationship between actual fundamental motor skill (FMS) proficiency, perceived motor confidence and competence, and physical activity (PA) among female children (n= 160; mean age = 10.69 ± 1.40 years). The Test of Gross Motor Development-2nd Edition (TGMD-2) was used to assess seven FMSs (locomotor, object-control, and stability). Motor confidence and competence were assessed using a valid skill-specific scale, and a modified version of the Self-Perception Profile for Children. PA levels were assessed using self-report (PA Questionnaire for Older Children (PAQ-C)) and classified as low, moderate, and high active. One-way and two-way ANOVAs (post-hoc honest significant difference (HSD)) and correlation coefficients were used to analyse the data. Findings indicate that the majority of youth (71.8%) were not meeting the minimum 60 min of daily PA recommended for health, and that 98.1% did not achieve the FMS proficiency expected for their age. While there were high levels of perceived physical self-confidence (PSC) reported within FMS skill-specific tasks, there was no significant correlation observed between actual FMS proficiency and perceived PSC among the cohort. Results show that low, moderately, and highly active female participants differ significantly in terms of their overall FMS (p = 0.03) and locomotor (LOC) control scores (p = 0.03). Results from a two-way between-groups analysis of variance also revealed no statistically significant interaction effect between PA grouping and physical performance self-concept (PPSC) on overall FMS proficiency levels. Results of a multiple linear regression indicate that perceived PSC is a significant predictor (beta = 0.183) of participants' overall PA levels. Data show a need for targeting low levels of PA, and low FMS proficiency in female youth, and for developing interventions aiming to enhance perceived PSC levels.